2016
DOI: 10.1002/ctpp.201500146
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Time Evolution of a Low Pressure Laboratory Plasma after Application of Transient high Voltage Positive Pulses

Abstract: The long‐time evolution of weakly‐collisional plasma with application of high voltage positive pulses to an electrode immersed in plasma, with pulse widths less than as well as more than ion plasma periods, is studied. The plasma is produced by electron impact ionization of argon or helium gas, where electrons are coming out from dc biased hot thoriated tungsten filaments. It is observed that during the temporal evolution of argon plasma, a beam component exists along with temporal bulk electrons giving rise t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…The observed results can also be understood qualitatively based on the past theoretical and experimental work in the low-pressure hot-filament discharge 3,10,[15][16][17] . Once the disk bias voltage is higher than the plasma potential (V b > V p ), bulk plasma electrons loss rate to the metal disk increases, resulting in increasing the plasma potential.…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“…The observed results can also be understood qualitatively based on the past theoretical and experimental work in the low-pressure hot-filament discharge 3,10,[15][16][17] . Once the disk bias voltage is higher than the plasma potential (V b > V p ), bulk plasma electrons loss rate to the metal disk increases, resulting in increasing the plasma potential.…”
Section: Discussionsupporting
confidence: 54%
“…It is expected to observe the plasma density enhancement if a positively biased (V b > V p ) disk electrode is immersed in the hot-filament helium discharge. Furthermore, the experimental device used in our study 15 was different than the double plasma device 10,11 therefore plasma response to a positively biased auxiliary electrode (disk) should be different than that reported in references [9][10][11] . Some of these open questions motivate us to perform experiments in the hot-filament helium discharge to see the effect of the positively biased auxiliary disk electrode on the plasma characteristics.…”
Section: Introductionmentioning
confidence: 67%
See 2 more Smart Citations
“…Choudhary et al [12] have reported the plasma density enhancement rather than reduction after application of transient high voltage positive pulses to the auxiliary electrode (metal disk) in low pressure hot-filament helium plasma. This study suggests that there should be a plasma density increment instead of reduction which was observed in the double plasma device [11] when a positively biased (V b >V p ) disk electrode is immersed in the hot-filament discharges.…”
Section: Introductionmentioning
confidence: 99%